2015
DOI: 10.2217/nnm.14.182
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Chemotherapy of Visceral Leishmaniasis by Lactoferrin-Appended Amphotericin B-Loaded Nanoreservoir: In Vitro and In Vivo Studies.

Abstract: Superior efficacy, desired stability and reliable safety of cost-effective LcfPGNP-AmB, suggest its potential for leishmaniasis therapeutics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 27 publications
0
24
0
Order By: Relevance
“…The reduction of zeta potential may be related to the encapsulation of AmB, which was identical to that of the previous studies. 41 Although zeta potential of drug-loaded micelles was lower than that of blank micelles, they all presented good dispersion and stability during the period of the experiment. Figure 2C exhibits the morphological observation of AmB/ …”
Section: Preparation and Characterization Of Micellesmentioning
confidence: 93%
“…The reduction of zeta potential may be related to the encapsulation of AmB, which was identical to that of the previous studies. 41 Although zeta potential of drug-loaded micelles was lower than that of blank micelles, they all presented good dispersion and stability during the period of the experiment. Figure 2C exhibits the morphological observation of AmB/ …”
Section: Preparation and Characterization Of Micellesmentioning
confidence: 93%
“…This approach may also be applicable for spleen selective drug targeting as splenic macrophages actively phagocytose red blood cells during hypersplenism and liver cirrhosis [84]. Research into the targeting of splenic and liver Leishmaniasis infections using nanoparticles may also be of potential strategic use [85, 86]. Standardized studies in animal models and pre-clinical trials measuring the efficacies of nanoparticle-based therapeutic agents will also be required for the development of novel spleen-selective therapeutic agents.…”
Section: Targeting Spleen For the Treatment Of Liver Cirrhosismentioning
confidence: 99%
“…Leishmania promastigotes use surface reductase at the time of ferric iron reduction to give access to the ferrous form. Previous studies have affirmed that the L. chagasi promastigote forms can use lactoferrin and transferrin iron for growth and metabolism (17)(18)(19). The findings have also suggested that the promastigote form has specific locations for connection between lactoferrin and transferrin.…”
Section: Discussionmentioning
confidence: 88%
“…Lactoferrin bonded with amphotericin B along with the LcfPGNP-AmB nanoparticle has anti-leishmaniasis effects, which decreases parasite burden in the spleen and increases immunity in the hamster. Iron is an essential nutrient for pathogen survival in the host cell (17)(18)(19). As a general strategy against microbes in mammals, the inhibitor complex system of iron has evolved to reduce the microbes access to iron.…”
Section: Discussionmentioning
confidence: 99%